Emerging Electronics and Automation Select Proceedings of the 3rd International Conference, E2A 2023, Volume 1 - Stroe, Daniel-Ioan; Nasimuddin, Dr; Laskar, Shahedul Haque; Pandey, Shivendra Kumar (Lecture Notes in Electrical Engineering, 2025)
XI, 344 p. 206 illus., 166 illus. in color.